An Update on the Molecular and Clinical Characteristics of Apocrine Carcinoma of the Breast - Semir Vranic (3353012) (2021)
Apocrine carcinoma of the breast is a rare malignancy. According to 2019 WHO classification, apocrine cellular features and a characteristic steroid receptor profile (Estrogen receptor (ER)-negative and androgen receptor (AR)-positive) define apocrine carcinoma. Her-2/neu protein expression is reported in ∼30-50% of apocrine carcinomas, while NGS analysis showed frequent PIK3CA/PTEN/AKT and TP53 mutations Followed by deregulation in the mitogen-activated protein kinase pathway components (mutations of KRAS, NRAS, BRAF). A recent miRNA study indicates various miRNAs (downregulated hsa-miR-145-5p and upregulated 14 miRNAs such as hsa-miR-182-5p, hsa-miR-3135b, and hsa-miR-4417) may target the commonly altered pathways in apocrine carcinomas such as ERBB2/HER2 and mitogen-activated protein kinase signaling pathway. Although AR expression is a hallmark of apocrine carcinoma, little is known regarding the efficacy/resistance to antiandrogens. Success of bicalutamide, a non-steroidal anti-androgen, was reported in a case of Her2-negative apocrine carcinoma. Two recent studies, however, described presence of anti-androgen resistance biomarkers (a splice variant ARv7 and AR/NCOA2 co-amplification) in a subset of AR+ apocrine carcinomas, cautioning the use of anti-androgens in AR+ triple-negative breast carcinomas. Apocrine carcinomas rarely show biomarkers predictive of response to immune checkpoint inhibitors (PD-L1 expression, MSI-H status, and TMB-high). Therefore, a comprehensive cancer profiling of apocrine carcinomas is necessary to identify potential therapeutic targets for a truly individualized treatment approach. Other Information Published in: Clinical Breast Cancer License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.clbc.2021.12.009